2013
DOI: 10.1016/j.rmed.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

FEV1 over time in patients with connective tissue disease-related bronchiolitis

Abstract: Summary Background Fibrosis or inflammation of the bronchioles is a well-known manifestation of connective tissue disease (CTD). However, the natural history of CTD-related bronchiolitis is largely unknown. Methods We analyzed consecutive patients evaluated at National Jewish Health (Denver, CO) from 1998 to 2008 with CTD and surgical lung biopsy-confirmed bronchiolitis. Linear mixed effects models were used to estimate the longitudinal postbronchodilator FEV1 %predicted (%pred) course and differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…This has also been observed in other studies [ 16 , 23 ] and may reflect the female predominance associated with rheumatoid arthritis. Interestingly, Fernandez Perez et al noted that male gender was an independent predictor of mortality in connective tissue disease-associated obliterative bronchiolitis [ 24 ]. Our study did not show a similar relationship between gender and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has also been observed in other studies [ 16 , 23 ] and may reflect the female predominance associated with rheumatoid arthritis. Interestingly, Fernandez Perez et al noted that male gender was an independent predictor of mortality in connective tissue disease-associated obliterative bronchiolitis [ 24 ]. Our study did not show a similar relationship between gender and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have noted that FEV1 was significantly lower in patients previously on D-penicillamine [ 19 ], we did not find evidence of worsening pulmonary impairment in patients on this agent. Fernandez Perez et al investigated the longitudinal progression of pulmonary function testing in patients with connective tissue disease associated-obliterative bronchiolitis [ 24 ]. While their study did not distinguish between underlying rheumatoid arthritis versus other connective tissue diseases, they discovered that the rate of FEV1 change was minimal during their three-year follow-up, regardless of therapy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prognosis is thought to be poor; however, in a recent prospective study in CTD-associated bronchiolitis (in which 50% of patients had RA), the forced expiratory volume in 1 second showed stability over time in both forms, suggesting that bronchiolitis associated with CTD may have a less aggressive course than idiopathic disease. 54,55 …”
Section: Forms Of Lung Disease In Rheumatoid Arthritismentioning
confidence: 99%
“…2,3 Among these, it has most commonly been described in rheumatoid arthritis and occasionally with Sjögren syndrome and systemic lupus erythematosus (SLE). 2,5 Cutaneous lupus erythematosus (CLE) is a localized autoimmune skin disorder that does not fulfill the required diagnostic criteria for SLE. 6 Cutaneous lupus erythematosus is no longer believed to represent a clinically homogenous skin-limited entity, as studies have reported that approximately 15% of CLE patients will progress toward SLE.…”
mentioning
confidence: 99%